(untitled) (Itinera, 2024)
The literary criticism has long been concerned with highlighting the importance of dreams in medieval literature, particularly in Boccaccio’s Decameron. However, the degree of horror that characterizes these dreams remains a relatively unexplored topic, often touched upon but rarely central in the contributions that have offered excellent interpre- tations of the dream narratives in Boccaccio’s text. Dissecting bodies, dividing and nar- rating them through disgusting and horrifying descriptions or circumstances is often a way to communicate the instability of the subject, to multiply it, and to render its identity mutable and changeable. Thus, this paper aims to investigate the ways in which horror in Boccaccio’s Decameron contributes to reforming subjectivities and (de)constructing the status of the characters. Attention will be paid to the stories where the narration of dis- turbing bodies intersects with the themes of dreams and visions. This perspective, which is always visual and situated in an otherworldly dimension, allows the characters to take on appearances far removed from an ideal image of an intact and healthy body. In fact, the bodies appear crucial in their destroyed carnality in a world – the dream world – that paradoxically is not populated by flesh. However, they serve as witnesses or warnings, bearers of truth, the more their appearance and flesh have been marred by torment. This paper intends to reflect on these topics.